Biological Aging Predicts Vulnerability to COVID-19 Severity in UK Biobank Participants. (4th March 2021) - Kuo, Chia-Ling; Pilling, Luke C; Atkins, Janice L; Masoli, Jane A H; Delgado, João; Tignanelli, Christopher; Kuchel, George A; Melzer, David; Beckman, Kenneth B; Levine, Morgan E
Abstract: Background: Age and disease prevalence are the 2 biggest risk factors for Coronavirus disease 2019 (COVID-19) symptom severity and death. We therefore hypothesized that increased biological age, beyond chronological age, may be driving disease-related trends in COVID-19 severity. Methods: Using the UK Biobank England data, we tested whether a biological age estimate (PhenoAge) measured more than a decade prior to the COVID-19 pandemic was predictive of 2 COVID-19 severity outcomes (inpatient test positivity and COVID-19-related mortality with inpatient test-confirmed COVID-19). Logistic regression models were used with adjustment for age at the pandemic, sex, ethnicity, baseline assessment centers, and preexisting diseases/conditions. Results: Six hundred and thirteen participants tested positive at inpatient settings between March 16 and April 27, 2020, 154 of whom succumbed to COVID-19. PhenoAge was associated with increased risks of inpatient test positivity and COVID-19-related mortality (ORMortality = 1.63 per 5 years, 95% CI: 1.43–1.86, p = 4.7 × 10 −13 ) adjusting for demographics including age at the pandemic. Further adjustment for preexisting diseases/conditions at baseline (ORM = 1.50, 95% CI: 1.30–1.73 per 5 years, p = 3.1 × 10 −8 ) and at the early pandemic (ORM = 1.21, 95% CI: 1.04–1.40 per 5 years, p = .011) decreased the association. Conclusions: PhenoAge measured in 2006–2010 was associated with COVID-19 severity outcomes more than 10 years later. These associations were partly accounted for by prevalent chronic diseases proximate to COVID-19 infection. Overall, our results suggest that aging biomarkers, like PhenoAge may capture long-term vulnerability to diseases like COVID-19, even before the accumulation of age-related comorbid conditions.